2011
DOI: 10.1007/s10653-011-9421-3
|View full text |Cite
|
Sign up to set email alerts
|

Release of beryllium from mineral ores in artificial lung and skin surface fluids

Abstract: Exposure to some manufactured beryllium compounds via skin contact or inhalation can cause sensitization. A portion of sensitized persons who inhale beryllium may develop chronic beryllium disease (CBD). Little is understood about exposures to naturally occurring beryllium minerals. The purpose of this study was to assess the bioaccessibility of beryllium from bertrandite ore. Dissolution of bertrandite from two mine pits (Monitor and Blue Chalk) was evaluated for both the dermal and inhalation exposure pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This investigation also reported that beryllium hydroxide was more soluble than BeO at both SLF pH levels. [4][5][6][7] for Research on Cancer. This is due to it causing genotoxic effects in a variety of types of eukaryotic cells, including human cells.…”
Section: Examples Of Other Dissolution Studiesmentioning
confidence: 99%
“…This investigation also reported that beryllium hydroxide was more soluble than BeO at both SLF pH levels. [4][5][6][7] for Research on Cancer. This is due to it causing genotoxic effects in a variety of types of eukaryotic cells, including human cells.…”
Section: Examples Of Other Dissolution Studiesmentioning
confidence: 99%
“…Beryllium metal has no relevant acute oral toxicity, it is not a skin sensitizer and it has low local irritation properties, the evidence for its carcinogenicity in animal studies is weak (4). The human exposure to beryllium and soluble beryllium compounds can occur during the commercial extraction and use (5), there is a weak information about its presence in house-dust (6). Some exposed individuals develop acute or chronic reaction to beryllium, based on their genetic disposition and the immune system functions.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies about the treatment of beryllium from varied beryllium ores, most of them are about beryl or gadolinite with high content of beryllium (beryllium oxide, 10%-12%) (Duling et al, 2012;Andreev et al, 2008;Saha, 1994a). But with increasing applications of beryllium and its compounds in science and technology, it is important to develop an efficient method for extracting beryllium from non-beryl beryllium ores or low content beryllium ores with high content of fluorine (F/BeO N 10%).…”
Section: Introductionmentioning
confidence: 99%